1999
DOI: 10.1017/s0022215100143877
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pregnancy on sensation of ear problems – ear problems associated with healthy pregnancy

Abstract: We wondered how many women had experienced a sensation of fullness in the ear during pregnancy. To address this question, data were obtained from a group of healthy women who attended the gynaecology clinic in our hospital as pregnancy cases between February 1995 and January 1998 and who volunteered to participate in our study. A control group was drawn from healthy female co-medical staff members of our hospital who had never been pregnant. The data used for comparing the two groups were taken from a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
1
13
0
3
Order By: Relevance
“…For example, throughout pregnancy, low-frequency audiometric thresholds significantly worsen, and during the third trimester, women perceive lower levels of sound as uncomfortably loud (Sennaroglu and Belgin, 2001). Self-reports and case studies indicate that other auditory symptoms, such as fullness in the ear, tinnitus, and autophonia, are more prevalent during pregnancy and symptoms resolve after giving birth (Gurr et al, 1993; Mukhophadhyay et al, 2007; Schmidt et al, 2010; Tsunoda et al, 1999). Physiological findings support these claims: Tandon et al (1990) found that ABR inter-peak intervals are prolonged during pregnancy.…”
Section: Estrogens Modulate Human Auditory Functionmentioning
confidence: 99%
“…For example, throughout pregnancy, low-frequency audiometric thresholds significantly worsen, and during the third trimester, women perceive lower levels of sound as uncomfortably loud (Sennaroglu and Belgin, 2001). Self-reports and case studies indicate that other auditory symptoms, such as fullness in the ear, tinnitus, and autophonia, are more prevalent during pregnancy and symptoms resolve after giving birth (Gurr et al, 1993; Mukhophadhyay et al, 2007; Schmidt et al, 2010; Tsunoda et al, 1999). Physiological findings support these claims: Tandon et al (1990) found that ABR inter-peak intervals are prolonged during pregnancy.…”
Section: Estrogens Modulate Human Auditory Functionmentioning
confidence: 99%
“…Tsunoda et al [9] investigated ear problems in a group of pregnant women and found that pure tone audiometry and impedance audiometry showed normal hearing in all cases. However, they did not mention the finding in different frequencies and also did not take into account the different stages of pregnancy.…”
Section: Audiological Changesmentioning
confidence: 99%
“…Changes in otoacoustic emissions and auditory evoked potentials in women using oral contraceptives suggest that the auditory system may become more masculine (McFadden, 2000). Hormone level variations that occur in pregnancy can provoke the feeling of fullness of the ear (Tsunoda et al, 1999) and low frequency hearing loss (Sennaroglu and Belgin, 2001) which resolves after delivery (Tsunoda et al, 1999). Also, the menstrual cycle seems to be reflected in changes in postural stability (Darlington et al, 2001) or brainstem evoked auditory responses Elkind-Hirsch et al, 1992a, b;Serra et al, 2003) or hearing thresholds (Swanson and Dengerink, 1988).…”
Section: Sex Hormones Affect the Inner Earmentioning
confidence: 99%